KEBIJAKAN FORMULASI MENGENAI PEMBUKTIAN TINDAK PIDANA PENCUCIAN UANG YANG TIDAK WAJIB DIBUKTIKAN TERLEBIH DAHULU TINDAK PIDANA ASALNYA - Musram Doso (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2021)
The anti money laundering law has been amended 3 (three) times, the most recent is Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering, however in its application it still raises debate, especially regarding whether or not the original criminal act is necessary. There are 2 issues raised in this study, namely whether the provisions of Article 69 of Law Number 8 of 2010 contradict the provisions of Article 2 paragraph (1) of Law Number 8 of 2010, and What is the formulation policy regarding investigation, prosecution and examination in court against TPPU which is not obliged to be proven beforehand the original criminal act. The purpose of this research is to find out, understand and analyze the provisions of Article 69 of Law Number 8 of 2010 which can be interpreted as contradicting the provisions of Article 2 paragraph (1) of Law Number 8 of 2010, and to formulate policies regarding investigation, prosecution and examination at court. court against TPPU which is not obliged to be proven in advance of the original criminal act. The conclusion is that the provisions of Article 2 paragraph (1) of the TPPU Law are inconsistent with the provisions of Article 69 of the TPPU Law. So that the debate regarding whether or not it is obligatory to prove the predicate crime before carrying out the investigation, prosecution and examination in court proceedings against TPPU can be ended immediately. With such a formula, it will result in mutual conformity between the provisions of Article 2 paragraph (1) of the TPPU Law and Article 69 of the TPPU Law